Both Alpha- and Beta-Rhizobia Occupy the Root Nodules of Vachellia karroo in South Africa - Beukes, Chrizelle W.; Boshoff, Francois S.; Phalane, Francina L.; Hassen, Ahmed I.; le Roux, Marianne M.; Stȩpkowski, Tomasz; Venter, Stephanus N.; Steenkamp, Emma T. (Frontiers in Microbiology, 2019)
Vachellia karroo (formerly Acacia karroo) is a wide-spread legume species indigenous to southern Africa. Little is known regarding the identity or diversity of rhizobia that associate with this plant in its native range in South Africa. The aims of this study were therefore: i) to gather a collection of rhizobia associated with V. karroo from a wide range of geographic locations and biomes; ii) to identify the isolates and infer their evolutionary relationships with known rhizobia; iii) to confirm their nodulation abilities by using them in inoculation assays to induce nodules under glasshouse conditions. To achieve these aims, soil samples were collected from 28 locations in seven biomes throughout South Africa, which were then used to grow V. karroo seedlings under nitrogen-free conditions. The resulting 88 bacterial isolates were identified to genus-level using 16S rRNA sequence analysis and to putative species-level using recA-based phylogenetic analyses. Our results showed that the rhizobial isolates represented members of several genera of Alphaproteobacteria (Bradyrhizobium, Ensifer, Mesorhizobium and Rhizobium), as well as Paraburkholderia from the Betaproteobacteria. Our study therefore greatly increases the known number of Paraburkholderia isolates which can associate with this southern African mimosoid host. We also show for the first time that members of this genus can associate with legumes, not only in the Fynbos biome, but also in the Albany Thicket and Succulent Karoo biomes. Twenty-six putative species were delineated among the 88 isolates, many of which appeared to be new to Science with other likely being conspecific or closely related to E. alkalisoli, M. abyssinicae, M. shonense and P. tropica. We encountered only a single isolate of Bradyrhizobium, which is in contrast to the dominant association of this genus with Australian Acacia. V. karroo also associates with diverse genera in the Grassland biome where it is quite invasive and involved in bush encroachment. Our findings therefore suggest that V. karroo is a promiscuous host capable of forming effective nodules with both alpha- and beta-rhizobia, which could be a driving force behind the ecological success of this tree species.